Pengaruh motivasi dan lingkungan kerja terhadap kinerja karyawan PT. Kanmo Retail Group Warehouse - Setiawan , Rio; Siamto, Wahadi; Ratnawati , Whina (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this research was to identify the relationship between motivation and work environment at the PT Kanmo Retail Group Warehouse in Bogor, West Java, from the perspective of both independent variables and their respective dependent variables, as well as to examine the interaction between the two. Quantitative descriptive analysis is performed with the help of statistical testing software (SPPS) to examine assumptions, hypotheses, and results from multiple regression analyses and coefficients of determination. This study concludes, in part and simultaneously, that the motivation and work environment at PT Kanmo Retail Group Ware House in Bogor have an influence on employee performance, with a coefficient of determination of 53.7%. The remaining 46.3% is influenced by other factors. The more effectively an organization manages its employees' needs for work motivation and a conducive work environment, the more effectively its employees will help it reach its goals.